Correction: Preparation of a fluorescent silver nanoprism–dye complex for detection of hydrogen peroxide in milk. Issue 18 (21st September 2015) - Peng, Chifang; Liu, Chunli; Xie, Zhengjun
<x xml:space="preserve">Abstract</x> Correction for 'Preparation of a fluorescent silver nanoprism–dye complex for detection of hydrogen peroxide in milk' by Chifang Peng et al., Anal. Methods, 2015, DOI: 10.1039/c5ay01261a.